Simulation of Energy Dump Converter Topology for Switched Reluctance Motors - Ayob, A; Abd Halim, S; Yusof, Y (International Journal of Engineering and Technology, 2018)
The switched reluctance machine (SRM) is the least expensive machine to produce yet it is very reliable.  An SRM drive system has to be designed so that there is integration between the machine and the converter-controller configuration. This paper focuses on the resistor dump converter topology where most of the energy from the windings is dissipated in a resistor. A detailed analysis and simulation of the converter has been conducted and a design guideline for the proposed converter is laid out.  The resistor dump converter has a low component count and this enables it to achieve a low cost converter.  Simulation results show that for the resistor dump converter additional snubbers are required.  This leads to an increase in complexity of the controller as more parameters need to be considered.  Also, the addition of the passive components of the snubber makes the circuit less reliable and costly. For the purpose of just looking into detail on the behaviour of the converter, it is sufficient to look at the results of the simulation using a static inductor to model the SP-SRM.  If cost is to be the priority, the most economical choice must be made but within limits of the application.